WORD FORMATION PROCESSES FOUND IN PADANG TRADING FORUM OF ANIMALS AND ANIMALS’ EQUIPMENT IN FACEBOOK - Andre Mutia; M. Zaim; Fitrawati Fitrawati (English Language and Literature, 2017)
This research focuses on word formation processes found in Forum Jual Beli Hewan dan Perlengkapan Hewan Kota Padang (Padang Facebook Trading Forum of Animals and Animals Equipment). The aims of this research are (1) to find types of word formation processes, and (2) to identify parts of speech of the terms involved. This research is a descriptive research. The results of the analysis of data are presented in the form of description and explanation. Data in this research were 95 special terms used in the activity of trading in FJB Hewan dan Perlengkapan Hewan Kota Padang. These data were gained and analyzed by means of observation and interpretation by the researcher. Results of the research show that there were nine processes of word formation involved in the creation of trading terms in FJB Hewan dan Perlengkapan Hewan Kota Padang. They were 34 borrowings (35,79%), 15 abbreviations (15.79%), 12 clippings (12.63%), 10 blendings (10, 53%), 9 compoundings (9,47%), 6 affixations (6,32%), 5 letter symbols (5,27%), 3 reduplications (3,16%), and 1 backformation (1,05%). Then, there were four parts of speech in which the trading terms belong to. They were 56 nouns (59%), 16 verbs (16.90%), 22 adjectives (23%), and 1 adverbs (1.05%).